The effectiveness of music therapy in increasing verbal creativity: systematic literature review : Efektivitas terapi musik dalam meningkatkan kreativitas verbal : systematic literature review - Supriyono, Lury Titiony; Muhid, Abdul (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
Music therapy can be used to increase a person’s verbal creativity. This study aims to describe music therapy increases verbal creativity. There are four research questions, namely: 1) Who is the subject who uses music therapy to increase verbal creativity, 2) What kind of music is used to increase verbal creativity, 3) How does music therapy play a role in increasing verbal creativity, 4) How does the success rate of music therapy increase verbal creativity. There were 11 kinds of literature reviewed in this study. Recommendations for further SLR research can be discussed regarding the views of counselors/therapists regarding music therapy for verbal creativity, improving the skills of music therapists using certain approaches, and developing music therapy for verbal creativity.